Intercultural communication difficulties and their effects on flight safety - Cheng, Ziying (2015)
Globalization of air travel is leading to a multicultural mix of crew. In regard of culture, the cockpit culture is more diverse than the past in aviation world. In the past 20 years, nearly all of the commercial airlines have recruited experienced international pilots in China. The study investigates intercultural communication difficulties experienced by international captains during their interactions with Chinese co-pilots in cockpit. Communication is the key for effective team work, while in multicultural team the role of communication is even more highlighted. Many researchers have explored pilot performance is more closely associated with the quality of interactive communication than with the technical proficiency. The objective of this study is to identify perspectives for calling the attention to the significance of communication challenges encountered by international captains and explore effective strategies to minimize insecure cultural factors due to intercultural communication barriers. This objective is explored through a qualitative research approach with semi-structured interviews in one of the major airlines in China. Thematic interviews were conducted in a face-to-face manner with 19 experienced international captains from varied countries and cultures. Through qualitative content analysis, a significant correlation between intercultural communication difficulties and flight safety was found.